Emerging Trends in Horticultural Crops: Role of Date Fruit in Promoting Urinary and Kidney Health - Mitanshu Singhal; Sofia Saifi; Aditi Rikhari (International Journal of Trends in Horticulture, 2026)
Dates, or Phoenix dactylifera L., have been widely consumed in different cultures, both as a food source and for their health benefits. Whereas dates have been reported extensively to improve cardiovascular, gastrointestinal, and metabolic function, their role in urinary tract and renal health has received lesser attention in mainstream nutritional sciences. This review systematically evaluates and synthesizes the current literature on the potential effects of dates to promote urinary health with respect to their specific antimicrobial, anti-inflammatory, antioxidant, and diuretic effects. Dates are especially high in bioactive compounds, such as flavonoids, tannins and phenolic acids with potent antioxidative and antimicrobial properties. Such phytochemicals have shown inhibitory action against the common uropathogens like Escherichia coli indicating their role in prophylaxis and treatment of recurrent urinary tract infection (UTIs). Moreover, nephroprotective effects in preclinical models suggest the potential of date extracts to attenuate oxidative stress and inflammatory damage in renal tissues, notably in models of chemically induced nephrotoxicity. Dates have a high potassium-to-sodium ratio and a low oxalate content enabling them to play a healthy role in the metabolism to create a favorable internal environment for kidney stone prevention. Certain strains have also been linked with mild diuretic effects, which can help to promote urination and expel pathogens and metabolic waste from the urinary tract. An extensive review of the potential functions of Phoenix dactylifera in kidney health and urinary tract function offers a foundation for future investigations as well as dietary recommendations in clinical medical practice.
Keywords: Kidneys; Nephroprotection; Phoenix dactylifera; Urinary Tract Infection; urinary health